1983
DOI: 10.1073/pnas.80.11.3168
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of a new human collagen with an extended triple-helical structural domain.

Abstract: The collagens are a family of major connective tissue proteins that are known to be the products of at least 11 distinct genes. Primary structural differences between the individual collagen types are thought to reflect functional diversity. We have isolated a previously unknown collagen gene product, termed "long-chain" (LC) collagen, from human chorioamniotic membranes by limited pepsin digestion. Comparison of the isolated a-chain subunit to the a chains of other collagen types by amino acid composition, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…Our best estimates, based on genomic Southern blot hybridization experiments and recombinant phage library screenings, are that C. elegans has at least 40 and as many as 150 distinct collagen genes. The number of collagen genes in C. elegans is much larger than that reported for any other organism, e.g., humans, in which 10 to 20 genes at most have been identified (3,4). In addition to their larger number, C. elegans collagen genes differ from other known collagen genes by their small size.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Our best estimates, based on genomic Southern blot hybridization experiments and recombinant phage library screenings, are that C. elegans has at least 40 and as many as 150 distinct collagen genes. The number of collagen genes in C. elegans is much larger than that reported for any other organism, e.g., humans, in which 10 to 20 genes at most have been identified (3,4). In addition to their larger number, C. elegans collagen genes differ from other known collagen genes by their small size.…”
Section: Discussionmentioning
confidence: 61%
“…Collagens have been extensively studied in vertebrates, in which at least nine collagen types, with specific tissue distributions and structural properties, have been described (3,4,16). Protein sequencing coupled with protease and chemical cleavage studies has shown that the different collagen types have unique primary sequences and are coded for by 10 to 20 genes (3, 4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, while type I collagen is the major collagen of bone, skin, tendons, and ligaments, type II collagen is found primarily in hyaline cartilage, and type IV collagen is the collagen of basement membranes. In addition, types III, V, VI, and VII collagens (1)(2)(3)(4)(5)(6)(7)(8)(9) show characteristic tissue distributions, which probably reflect their specific functions in different tissues.…”
mentioning
confidence: 99%
“…All collagens share a characteristic amino acid sequence which can be represented as (Gly-X-Y), where X and Y can be any amino acids but are often proline or hydroxyproline. Collagens have been extensively studied in vertebrates, for which at least nine collagen types with different protein sequences and tissue distributions have been described (3,5). For the past few years, we have been studying the collagen gene family of the soil nematode Caenorhabditis elegans.…”
mentioning
confidence: 99%